Scholar/familiar education and Maroccan couples. Diachronic study of Casablanca region (Foro de Educacion, 2011)
Moroccan marriages have experienced relevant changes in the former decades. These transformations are closely linked to issues such as the couple academic background, women incorporation to the labour market with related incomes, or governmental policy devoted to gender equality.In our analysis we intend to highlight the major changes and transformations developed in the fields of family and education of Moroccan couples in the geographical region of Casablanca (Morocco). In order to gather data concerning those issues, we have undertaken a comparative diachronic study focused on those aspects in the two chronological moments of the years 1986 and 2007. In relation to the methodological ap- proach of our analysis, we have used as main instruments of data collection a mixed questionnaire, several interviews and direct observation.The conclusions of our analysis are sound and clear. It can be stated that, in spite of the relevance of the changes occured in the fields of family and education in Moroccan society, currently men and women still develop clearly distinct roles and functions in the familiar institution, in the context of a society charac- terized by the extremely important role of women in the education of Moroccan children.